Leveraging Marketing Intelligence to Enhance University Performance - Mukti Al Ghozali, Caesar; Wahyuning Astuti, Sri (Escalate : Economics and Business Journal, 2025)
This study aims to examine the impact of marketing intelligence on university performance, with a focus on the mediating roles of knowledge utilization effectiveness and strategic decision quality. Employing a quantitative research design, data were collected from academic and administrative staff at the Akademi Penerbang Indonesia Banyuwangi and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that marketing intelligence has a significant influence on both knowledge utilization and strategic decision quality, which in turn positively affect university performance. While direct effects from market sensing capability and marketing analytics capability on performance were not significant, their indirect effects through marketing intelligence were substantial. Competitor intelligence was found to be a strong predictor of marketing intelligence. These results underscore the pivotal role of marketing intelligence as a strategic capability, enabling universities to transform external insights into informed decisions and enhanced institutional outcomes. The study contributes to the higher education management literature by offering a comprehensive model that links marketing functions to academic performance through strategic mechanisms.